Investigation on the release of residual stress in a folded structure applied to MEMS devices. (15th July 2021) - Tang, Chuying; Yu, Hongyu; Sun, Chengliang; Zhang, Yi; Wang, Liang; Cai, Yao; Wu, Jingyi; Wang, Qing; Liu, Sheng
Abstract: During MEMS device fabrication process, the residual stress of thin film caused by thermal expansion coefficient mismatch and lattice mismatch is an important factor that will deteriorate the properties of thin film and bring yield losses to MEMS devices. In this work, a method to release the residual stress by using a folded structure with V‐shaped grooves is proposed. The folded structures with different groove width and groove interval are fabricated and relative Raman frequency shift is adopted to calculate the residual stress. The minimum residual thermal stress of 11.6 MPa can be obtained in the folded structure models by simulation, which is about five times lower than the residual thermal stress of the flat structure. The minimum residual stress of 40 MPa can be obtained in the folded structure by experiment results, which is about 20 times lower than the residual stress of the flat structure. The simulation results and experimental analysis confirms that introducing a folded structure with groove into the design of MEMS device is an effective way to suppress the generation of residual stress, thus enhancing the reliability of MEMS devices.